2000
DOI: 10.1021/bi000013p
|View full text |Cite
|
Sign up to set email alerts
|

Role of Side-chains in the Cooperative β-Hairpin Folding of the Short C−Terminal Fragment Derived from Streptococcal Protein G

Abstract: A short C-terminal fragment of immunoglobulin-binding domain of streptococcal protein G is known to form nativelike beta-hairpin at physiological conditions. To understand the cooperative folding of the short peptide, eight Ala-substituted mutants of the fragment were investigated with respect to their structural stabilities by analyzing temperature dependence of NMR signals. On comparison of the obtained thermodynamic parameters, we found that the nonpolar residues Tyr45 and Phe52 and the polar residues Asp46… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

12
139
0

Year Published

2004
2004
2010
2010

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 100 publications
(151 citation statements)
references
References 47 publications
12
139
0
Order By: Relevance
“…These include hydrogen bonds, electrostatic interaction, turn preference, and hydrophobic packing of side chains (37)(38)(39)(40)(41). The wide range of thermal melting temperatures observed for trpzips (including the GB1 ␤-hairpin) is consistent with the idea that a stable ␤-hairpin results from an intricate interplay among several factors.…”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…These include hydrogen bonds, electrostatic interaction, turn preference, and hydrophobic packing of side chains (37)(38)(39)(40)(41). The wide range of thermal melting temperatures observed for trpzips (including the GB1 ␤-hairpin) is consistent with the idea that a stable ␤-hairpin results from an intricate interplay among several factors.…”
Section: Discussionsupporting
confidence: 62%
“…Munekata and coworkers (39) recently have shown that a characteristic hydrogen bond network in the loop region (i.e., DDATKT) of the GB1 ␤-hairpin, which involves mostly D46, T49, and K50, is important for its stability because most single mutations in this region destabilize the ␤-hairpin conformation. A similar hydrogen bond network can also be found in the GB1 turn region of its parent protein, protein G (42).…”
Section: Discussionmentioning
confidence: 99%
“…The native hydrophobic cluster contains two chemical shift probes of folding. Kobayashi and coworkers (23,(28)(29)(30) have long recognized the value of the Tyr-5-H␦ and Val-14-H␥ up resonance shifts for measuring the folding equilibrium of GB1 hairpin analogs. In our recent examination of more stable analogs this continued to be the case.…”
Section: Resultsmentioning
confidence: 99%
“…We present results for the folding of the model system corresponding to the C-terminal peptide from the B1 domain of protein G (the G peptide), which is known to form a ␤-hairpin structure in solution (34) and has been the subject of previous experimental (35)(36)(37) and computational (7, 8, 12-17, 20, 21, 30, 32, 33, 38) studies. Two mechanisms for G-peptide formation have been previously proposed: the zipper model (35) and the hydrophobic collapse model (20,36,37).…”
mentioning
confidence: 99%
“…Two mechanisms for G-peptide formation have been previously proposed: the zipper model (35) and the hydrophobic collapse model (20,36,37). These models describe the sequence of ␤-hairpin hydrogen bond formation and association of hydrophobic core residues.…”
mentioning
confidence: 99%